Improving trigonometric competency with GeoGebra: a quasi-experimental study in a high school - Carriazo-Regino, Yulieth; Hurtado-Carmona, Dougglas; Bermudez-Quintero, Andrés (Institute of Advanced Engineering and Science, 2024)
This quasi-experimental study examines the efficacy of GeoGebra in enhancing trigonometric competence among tenth-grade students in Montería, Colombia. Comparing an experimental group that used GeoGebra with a control group receiving traditional teaching, key competencies such as reasoning and argumentation, communication, representation and modeling, and problem posing and solving were evaluated. Pre-intervention results showed that 88.19% of students in the experimental group had insufficient performance in reasoning and argumentation. After the implementation of GeoGebra, this figure decreased to 5.5%. In competencies of communication, representation, and modeling, the insufficient performance reduced from 85.7% to 5.5%, and in problem posing and solving, from 80.3% to 5.7%. These significant improvements demonstrate the positive impact of GeoGebra on the development of mathematical competencies. The study concludes that GeoGebra is an effective tool for strengthening trigonometric competence in high school students, highlighting the importance of integrating digital technologies in mathematics education. The findings suggest the need for more research on the use of technological tools in mathematics education and support investment in technological resources and teacher training.